PENGARUH MOTIVASI, RELATIONSHIP MARKETING DAN SERVICE QUALITY TERHADAP KEPUTUSAN PEMBELIAN GEN Z MUSLIM DI KAB. SINJAI DENGAN LOYALITAS KONSUMEN SEBAGAI VARAIBEL INTERVENING PADA SHOPEE - Dewi, Maharani; Muchlis, Mustakim; Ikbal, Muhammad (Jurnal Ilmiah Ekonomi Dan Bisnis, 2024)
This study aims to determine the relationship between motivation, relationship marketing and service quality on purchasing decisions of Muslim Gen Z with consumer loyalty as an intervening variable. This study is a quantitative, causal associative study. Data were obtained through direct distribution of questionnaires to 230 respondents who are Muslim Gen Z in Sinjai Regency. The analysis method used is SEM-PLS. The results of the study found that motivation and relationship marketing have a positive but not significant effect on purchasing decisions. While service quality and consumer loyalty have a positive and significant effect on purchasing decisions. On the other hand, motivation, relationship marketing and service quality have a positive and significant effect on purchasing decisions of Muslim Gen Z through consumer loyalty as an intervening variable on Shopee. This shows that companies should focus on improving service quality and building consumer loyalty, as both have a significant impact on purchasing decisions. Relationship marketing strategies and understanding consumer motivation need to be optimized to strengthen loyalty, which in turn improves purchasing decisions.